The characterisation of geosynthetic interface friction by means of the inclined plane test. Issue 1 (February 2021) - Pavanello, P.; Carrubba, P.; Moraci, N.
Abstract: The paper focuses on the evaluation of the shear strength in conditions of low normal stress of various geosynthetic-geosynthetic interfaces, which are typical of landfill cover systems, by means of the inclined plane test, with the aim of studying the friction mobilisation in relation to various kinematic behaviours. The results of three different methods to evaluate the angle of friction were analysed, together with the sensitivity of the interfaces in relation to the wear effect and the influence of the state of hydration. The results showed very different responses of the interfaces to the shear stress, which involved three main types of sliding mechanisms, referred to as sudden, gradual and uneven sliding. Another outcome observed was that the shear strength of geosynthetic-geosynthetic interfaces cannot always be properly characterised following the procedure proposed by the European standard for soil-geosynthetic interfaces (EN ISO 12957–2), since the actual mobilised kinematic behaviour should be taken into consideration. In this regard, the paper provides some hints on the choice of the more representative parameter of friction for each type of sliding. A particular focus was given to the case of gradual sliding interfaces, for which the static friction is difficult to detect due to the very slow movements; for practical purposes, the design friction of these interfaces should be evaluated by using an adequate safety factor with respect to the friction evaluated at 1 mm of displacement. Highlights: The paper offers a comparison of the results of three different methods to evaluate the angle of interface friction at low normal stress by means of the inclined plane test for various interfaces, considering alsowearing and hydration state. The research highlights the response of the interfaces to the shear stress may be very different, involving various sliding mechanisms. These kinematics cannot be revealed by the common direct shear test, in which the speed is imposed by the apparatus. From this point of view, the inclined plane device allows increasing stress state rather than imposed strain rate. The results show that the shear strength of geosynthetic-geosynthetic interfaces cannot be correctly characterised if the real sliding kinematics is not taken into consideration. The paper provides some hints on the choice of the more representative parameter of friction, for design purposes, according to the various interface behaviours.